Changes in the Gene Expression Pattern Induced by 2-Methoxyestradiol in the Mouse Uterus - Cardenas-Sankan, G; Orihuela-Diaz, P; Reuquen-Lopez, P; Diaz-Saldivar, P; Orostica, M (2012)
Sin Editorial Disponible